2010
DOI: 10.2165/11536850-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Movement Skills in Children and Adolescents

Abstract: The mastery of fundamental movement skills (FMS) has been purported as contributing to children's physical, cognitive and social development and is thought to provide the foundation for an active lifestyle. Commonly developed in childhood and subsequently refined into context- and sport-specific skills, they include locomotor (e.g. running and hopping), manipulative or object control (e.g. catching and throwing) and stability (e.g. balancing and twisting) skills. The rationale for promoting the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
1,050
7
82

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,207 publications
(1,177 citation statements)
references
References 50 publications
38
1,050
7
82
Order By: Relevance
“…Thus, possible differences between genders might have biased the results. Third, the variability concerning the body weight among the participants was also a limitation, since weight status is associated with motor coordination [6]. Nevertheless, the study adds to the underexplored literature on the relationship between motor coordination and sports performance in adolescent non-athletes.…”
Section: Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, possible differences between genders might have biased the results. Third, the variability concerning the body weight among the participants was also a limitation, since weight status is associated with motor coordination [6]. Nevertheless, the study adds to the underexplored literature on the relationship between motor coordination and sports performance in adolescent non-athletes.…”
Section: Limitationsmentioning
confidence: 97%
“…However, the usefulness of measures obtained from motor coordination tests is not restricted to solely assessing the neurological and functional status in children [3]. For instance, emerging evidence supports associations between the degree of motor coordination and a range of health outcomes among boys and girls [4,5], such as levels of physical activity, physical fitness, and weight status [6].…”
Section: Introductionmentioning
confidence: 99%
“…Given that both childhood overweight and obesity as well as lower motor skill levels have been linked with less active lifestyles (24)(25)(26)(27), PA might act as an important mediator (8,28,29). As noted by Wrotniak et al (30), children with poorer motor skills are less likely to be physically active and probably drawn to more sedentary pursuits, which subsequently may lead to the development of overweight and obesity.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence from multiple cross-sectional studies clearly indicates an inverse association between both factors (8,9). Regardless of motor assessment tool and body mass index (BMI) based classification method being used, lower fundamental motor skill mastery (i.e., qualitative measures related to movement execution) as well as poorer performances on gross motor skill and coordination tests (i.e., quantitative measures related to motor outcome) have been consistently reported in overweight and obese children as compared to healthy-weight peers and/or age-related standards (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The role of motor competence in children's physical activity levels has been conceptualized in a theoretical model by Stodden et al (2008; recently revised by Robinson et al in 2015). Numerous studies have confirmed the proposed positive relationship between children's motor competence and their physical activity levels (e.g., Holfelder & Schott, 2014;Logan et al, 2014;Lubans, Morgan, Cliff, Barnett, & Okely, 2010). …”
Section: Introductionmentioning
confidence: 99%